World book 2001. Vol. 19 T / Mary Alice Anderson - Anderson, Mary Alice (Estados Unidos de América: World book, Inc, 2001)
Additional resources, early life, political and public career, important dates in Taft's life, facts in brief, Tanzania, government, people economy, history, how tape recorders work, main kinds of tariffs, why tariffs are levied, arguments against tariffs, principles of taxation, taxation in the united states, taxation in Canada, tay-sachs disease, early life, military career, nomination for president, Taylor's life.
Portada ilustrada, mapa, cuadro
Col. Enc
Keywords: 1. ENCICLOPEDIA 2. WORLD BOOK T VOL.19 3. REFERENCIA